2021
DOI: 10.1177/23779608211035209
|View full text |Cite
|
Sign up to set email alerts
|

Strategies Adopted by Novice Nurse Educators to Facilitate Their Transition From Practice to Academia: A Qualitative Study in Ghana

Abstract: Introduction The successful transition of nurses from clinical practice to academia is essential to the training of a proficient future nursing workforce. However, deprived of requisite support and guidance, novice nurse educators often find the transition from bedside nursing practice to the classroom challenging and hence, adopt some coping strategies to facilitate their transition. Yet, little is known about the strategies adopted by Ghanaian novice nurse educators to facilitate their transition. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…From the responses from respondents, there are numerous challenges encountered by clinical radiography as they transited to academic educators. These were collaborated by many other resaech findings and include but not limited to rigorous research activities (Thompson and Taylor, 2020), most conferences and workshops were self-sponsored (Laari et al, 2021), involvement in academic activities, poor working conditions, that being an academic educator does not give more time to spend with their family and reduction of salary earned by a clinical radiographer who transits to be an academic educator. This agrees with the finding by Laari et al (2021) deprived of requisite support and guidance, novice nurse educators often find the transition from Salud, Ciencia y Tecnología.…”
Section: Discussionmentioning
confidence: 99%
“…From the responses from respondents, there are numerous challenges encountered by clinical radiography as they transited to academic educators. These were collaborated by many other resaech findings and include but not limited to rigorous research activities (Thompson and Taylor, 2020), most conferences and workshops were self-sponsored (Laari et al, 2021), involvement in academic activities, poor working conditions, that being an academic educator does not give more time to spend with their family and reduction of salary earned by a clinical radiographer who transits to be an academic educator. This agrees with the finding by Laari et al (2021) deprived of requisite support and guidance, novice nurse educators often find the transition from Salud, Ciencia y Tecnología.…”
Section: Discussionmentioning
confidence: 99%
“…From the responses from respondents, there are numerous challenges encountered by clinical radiography as they transited to academic educators. These were collaborated by many other resaech findings and include but not limited to rigorous research activities (Thompson and Taylor, 2020), most conferences and workshops were self-sponsored (Laari et al, 2021), involvement in academic activities, poor working conditions, that being an academic educator does not give more time to spend with their family and reduction of salary earned by a clinical radiographer who transits to be an academic educator. This agrees with the finding by Laari et al (2021) who reported that workshops and conferences help build their confidences and eases to academic educator despite been self-sponsor, which is in line with the study.…”
Section: Discussionmentioning
confidence: 99%
“…These were collaborated by many other resaech findings and include but not limited to rigorous research activities (Thompson and Taylor, 2020), most conferences and workshops were self-sponsored (Laari et al, 2021), involvement in academic activities, poor working conditions, that being an academic educator does not give more time to spend with their family and reduction of salary earned by a clinical radiographer who transits to be an academic educator. This agrees with the finding by Laari et al (2021) who reported that workshops and conferences help build their confidences and eases to academic educator despite been self-sponsor, which is in line with the study.…”
Section: Discussionmentioning
confidence: 99%
“…However, transitional support programmes and interventions are mostly in the developed countries (Nowell et al, 2017 ; Shieh & Cullen, 2019 ) with little emphasis placed on interventions required to ease the transition in Africa (Seekoe, 2016 ; Sodidi & Jardien‐Baboo, 2020 ). In the Ghanaian context, the situation is no different and often results in difficult and stressful transitions (Laari, Apiribu, Gazari, et al, 2021 ). The absence thereof and inadequate transition support programmes also deepen the challenge of suboptimal teaching competencies in this novice population of nurse educators (Heydari et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, nurse educators are usually recruited from the clinical setting and posted to HTIs to teach (Laari, Apiribu, Amooba, et al, 2021 ). However, the absence of transition support programmes coupled with failure to meet the WHO requirements for nurse educators makes the transition more difficult (Laari, Apiribu, Gazari, et al, 2021 ). Hence, it is imperative to explore NNEs' perspectives on easing the transition from nurse clinician to nurse educator in Ghana.…”
Section: Introductionmentioning
confidence: 99%